Buprenorphine and opioid antagonism, tolerance, and naltrexone-precipitated withdrawal - Paronis, Carol A; Bergman, Jack (The Journal of pharmacology and experimental therapeutics, 2011)
The dual antagonist effects of the mixed-action μ-opioid partial agonist/κ-opioid antagonist buprenorphine have not been previously compared in behavioral studies, and it is unknown whether they are comparably modified by chronic exposure. To address this question, the dose-related effects of levorphanol, trans-(-)-3,4-dichloro-N-methyl-N-[2-(1-pyrrolidinyl)cyclohexyl] benzeneacetamide (U50,488), heroin, and naltrexone on food-maintained behavior in rhesus monkeys were studied after acute and chronic treatment with buprenorphine (0.3 mg/kg/day). In acute studies, the effects of levorphanol and U50,488 were determined at differing times after buprenorphine (0.003-10.0 mg/kg i.m.). Results show that buprenorphine produced similar, dose-dependent rightward shifts of the levorphanol and U50,488 dose-response curves that persisted for ≥ 24 h after doses larger than 0.1 mg/kg buprenorphine. During chronic treatment with buprenorphine, the effects of levorphanol, U50,488, heroin, and naltrexone were similarly determined at differing times (10 min to 48 h) after intramuscular injection. Overall, results show that buprenorphine produced comparable 3- to 10-fold rightward shifts in the U50,488 dose-response curve under both acute and chronic conditions, but that chronic buprenorphine produced larger (10- to ≥ 30-fold) rightward shifts in the heroin dose-effect function than observed acutely. Naltrexone decreased operant responding in buprenorphine-treated monkeys, and the position of the naltrexone dose-effect curve shifted increasingly to the left as the time after daily buprenorphine treatment increased from 10 min to 48 h. These results suggest that the μ-antagonist, but not the κ-antagonist, effects of buprenorphine are augmented during chronic treatment. In addition, the leftward shift of the naltrexone dose-effect function suggests that daily administration of 0.3 mg/kg buprenorphine is adequate to produce opioid dependence.